2021
DOI: 10.14710/jksa.24.1.9-14
|View full text |Cite
|
Sign up to set email alerts
|

Aluminum Pillared Clay (Al-PILC) for Adsorption of Dyes in Red Fruit Oil

Abstract: Red fruit oil contains carotene, which is dark orange, so it is not very popular. Therefore, it is necessary to reduce the intensity of the color. Yesterday, in this study, the synthesis and characterization of Al-pillared clay (Al-PILC) from light and heavy clay fractions were carried out. The absorption capacity of red fruit carotene dyes was studied. The research stages included preparation, fractionation, activation, pillarization of clay with aluminum, characterization, and adsorption test for carotene dy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…Our sample of clay types 1:1 (kaolinites) absorbs for the initial concentrations of 20 mg/L for the raw, bridged and activated acid states respectively 0.875; 0.912 and 0.951 mmol/g for example indicates that it is not a structural phenomenon, but rather a surface interaction [34]. Acid activation causes a slight increase in specific surface area; the bridging leads to a deposit of polycations on the surface of the kaolinites and increase a little bit the basal spacing [35] [36]. The samples are of different texture (specific surface and porosity) and the adsorbed quantities are not always closely related to the texture; it can therefore be concluded that the texture has no significant influence on the adsorption of carotenes.…”
Section: Effect Of Contact Time On Adsorption Kineticsmentioning
confidence: 99%
“…Our sample of clay types 1:1 (kaolinites) absorbs for the initial concentrations of 20 mg/L for the raw, bridged and activated acid states respectively 0.875; 0.912 and 0.951 mmol/g for example indicates that it is not a structural phenomenon, but rather a surface interaction [34]. Acid activation causes a slight increase in specific surface area; the bridging leads to a deposit of polycations on the surface of the kaolinites and increase a little bit the basal spacing [35] [36]. The samples are of different texture (specific surface and porosity) and the adsorbed quantities are not always closely related to the texture; it can therefore be concluded that the texture has no significant influence on the adsorption of carotenes.…”
Section: Effect Of Contact Time On Adsorption Kineticsmentioning
confidence: 99%